Pengolahan Limbah Cair Industri Pewarna Makanan Secara Koagulasi dan Adsorpsi - Fitria Nanda Febrianti; Fendi Fradana; Kartika Udyani (Journal of Industrial Process and Chemical Engineering (JOICHE), 2023)
The liquid waste produced by the food coloring industry contains quite dense colors, so it needs to be processed before being discharged into the environment. The study aims to determine the effect of aloe vera coagulant doses on removal, to determine the effect of activated carbon on color removal. Liquid waste is waste or residue from an activity or business that is in liquid form and contains various kinds of materials that can pose a hazard to water if disposed of immediately. The research method consisted of making aloe vera solution followed by coagulation using aloe vera solution and adsorption of color waste using activated carbon. The results showed that the addition that produced the highest color removal in the coagulation process was 1.2% coagulant dose. The mass of activated carbon which produced the highest removal was 62.5% with a removal of 95%.